Synthesis of α-Chloroarylacetic Acid via Electrochemical Carboxylation of α,α-Dichloroarylmethane Derivatives - Corentin Maret; Nicolas David; David Pierrot; Eric Léonel; Vincent Levacher; Jean-François Brière; Sylvain Oudeyer (Molecules, 2023)
The electrocarboxylation of α,α-dichloroarylmethane derivatives in the presence of CO2 was achieved, providing several α-chloroarylacetic acid derivatives with modest yields but high selectivity (chlorinated vs. non-chlorinated or dicarboxylic acid products). The obtained products were then involved in several chemical transformations, underlining their potential as versatile intermediates in synthetic chemistry. A mechanism was also proposed based upon a control experiment and cyclic voltammetry (CV) study.